SOME PARADOXES OF INCONSISTENCIES BETWEEN THE RESULTS OF TESTS OF "RESIDUAL KNOWLEDGE" OF A STUDENT AND STUDENTS AT A UNIVERSITY IN THE CONTEXT OF CHOOSING DIDACTIC GOALS OF VALUE-BASED TIME MANAGEMENT (Scientific journal of the Fergana State University, 2024)
This article deals with psychological and pedagogical foundations and theoretical and methodological substantiation of existing paradoxes of imbalance between conditionally "programmed formative knowledge" and diagnosed real results and taking into account these factors when implementing didactic goals of motivational and developmental value and meaningful time management in the relationship of universities with other pre-university educational institutions. In order to clarify causal factors describing these problematics, the article provides a comparative analysis of sources and methods of achieving basic knowledge formation in the context of value and meaningful time management, given the program goals of training new formation specialists in the innovative environment of higher education institution. Herewith it is offered, that at each stage of training it is necessary to carry out prognostication and diagnostics of educational achievements of students - future specialists from the position of implementation of system regulative, considering interrelations of intellectual possibility of personality in the conditions of realization of motivating-developing technologies of time management of multivariant training in a higher school.